2015
DOI: 10.4049/jimmunol.1501524
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Reprogramming of Circulating Memory T Follicular Helper Cell Function during Chronic HIV Infection

Abstract: Despite the overwhelming benefits of antiretroviral therapy (ART) in curtailing viral load in HIV infected individuals, ART does not fully restore cellular and humoral immunity. HIV infected individuals under ART show reduced responses to vaccination and infections and are unable to mount an effective anti-viral immune response upon ART cessation. There are many factors that contribute to these defects including persistent inflammation, especially in lymphoid tissues, where T follicular helper (Tfh) cells inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 42 publications
13
89
0
Order By: Relevance
“…Unexpectedly, this study showed that the emergence of HIV-1 antibodies with broader neutralizing breadth in HIV-1 controllers was associated with Tfh-like cells expressing CXCR3, a surface marker denoting cells considered less efficient in supporting B cell Ig class switching in previous in vitro studies (15)(16)(17)(18). While our observations confirm that CXCR3 + Tfh-like cells are inferior to CXCR3 -Tfh-like cells in supporting IgG1 class switching, we did demonstrate that CXCR3 + Tfh-like cells have abilities to induce class switching to IgG3 and to alternative Ig subtypes, to secrete high levels of B cell-supporting cytokines, and to induce phenotypical maturation of B cells at equivalent levels as CXCR3 -Tfh-like cells, at least when analyzed over a longer, 6-day co-incubation period with total B cells and SEB stimulation, and not just in a short-term culture assay lasting for 48 hours (15 + Tfh-like cells in maintaining or expanding preexisting B cell responses, but not in the initial priming of new antigen-specific B cells, was also hypothesized in alternative contexts associated with limited antigen exposure, such as in recipients of vaccines against influenza (19).…”
Section: Cxcr3mentioning
confidence: 67%
See 4 more Smart Citations
“…Unexpectedly, this study showed that the emergence of HIV-1 antibodies with broader neutralizing breadth in HIV-1 controllers was associated with Tfh-like cells expressing CXCR3, a surface marker denoting cells considered less efficient in supporting B cell Ig class switching in previous in vitro studies (15)(16)(17)(18). While our observations confirm that CXCR3 + Tfh-like cells are inferior to CXCR3 -Tfh-like cells in supporting IgG1 class switching, we did demonstrate that CXCR3 + Tfh-like cells have abilities to induce class switching to IgG3 and to alternative Ig subtypes, to secrete high levels of B cell-supporting cytokines, and to induce phenotypical maturation of B cells at equivalent levels as CXCR3 -Tfh-like cells, at least when analyzed over a longer, 6-day co-incubation period with total B cells and SEB stimulation, and not just in a short-term culture assay lasting for 48 hours (15 + Tfh-like cells in maintaining or expanding preexisting B cell responses, but not in the initial priming of new antigen-specific B cells, was also hypothesized in alternative contexts associated with limited antigen exposure, such as in recipients of vaccines against influenza (19).…”
Section: Cxcr3mentioning
confidence: 67%
“…The results presented here suggest that a similar developmental hierarchy also exists within the pools of circulating Tfh-like cells, and that PD-1 lo Tfh cells represent a longlived precursor cell population that can replenish the more mature and short-lived PD-1 hi effector Tfh cells. Interestingly, these PD-1 lo Tfh-like cells included a substantial proportion of CD45RO -naive-like T cells, a cell population that was excluded in prior studies (15)(16)(17) but includes a fraction of highly immature memory T cells with increased stem cell-like properties (36). The ability to maintain a larger proportion of PD-1 lo memory Tfh-like cells that are enriched for a T memory stem cell phenotype relative to PD-1 hi pTfh cells could represent a distinct aspect of HIV-1 controllers with more broadly neutralizing antibody responses, and appears to separate these patients from HIV-1 progressors, in whom high-level viremia may lead to more differentiated and possibly more exhausted PD-1 hi pTfh cell populations (52).…”
Section: Cxcr3mentioning
confidence: 99%
See 3 more Smart Citations